Nonlinear Vibration of Oscillation Systems using Frequency-Amplitude Formulation - A. Fereidoon; M. Ghadimi; A. Barari; H.D. Kaliji; G. Domairry (Shock and Vibration)
In this paper we study the periodic solutions of free vibration of mechanical systems with third and fifth-order nonlinearity for two examples using He's Frequency-Amplitude Formulation (HFAF).The effectiveness and convenience of the method is illustrated in these examples. It will be shown that the solutions obtained with current method have a fabulous conformity with those achieved from time marching solution. HFAF is easy with powerful concepts and the high accuracy, so it can be found widely applicable in vibrations, especially strong nonlinearity oscillatory problems.